Ray fractions and carbohydrate dynamics of tree species along a 2750 m elevation gradient indicate climate response, not spatial storage limitation. Issue 6 (30th January 2020) - Godfrey, Jessie M.; Riggio, Jason; Orozco, Jessica; Guzmán‐Delgado, Paula; Chin, Alana R. O.; Zwieniecki, Maciej A.
Summary: Parenchyma cells in the xylem store nonstructural carbohydrates (NSC), providing reserves of energy that fuel woody perennials through periods of stress and/or limitations to photosynthesis. If the capacity for storage is subject to selection, then the fraction of wood occupied by living parenchyma should increase towards stressful environments. Ray parenchyma fraction (RPF) and seasonal NSC dynamics were quantified for 12 conifers and three oaks along a transect spanning warm dry foothills (500 m above sea level) to cold wet treeline (3250 m asl) in California's central Sierra Nevada. Mean RPF was lower for both conifer and oak species with warmer dryer ranges . RPF variability increased with elevation or in relation to associated climatic variables in conifers – treeline‐dominant Pinus albicaulis had the lowest mean RPF measured ( c. 3.7%), but the highest environmentally standardized variability index. Conifer RPF variability was explained by environment, increasing predominantly towards cooler wetter range edges. In oaks, NSC was explained by environment – values increasing for evergreen and decreasing for deciduous oaks with elevation. Lastly, all species surveyed appear to prioritize filling available RPF with sugar to achieve molarities that balance reasonable tensions over starch to maximize stored carbon. RPF responds to environment but is unlikely to spatially constrain NSC storage.